Implementation of a Moodle-Based Learning Management System (LMS) to Stimulate Self-Regulated Learning (SRL) in Guidance Institution Students Civil Service School Selection - Avandhi Surya Setia; Yudan Hermawan; A. Hasdiansyah (Educia Journal, 2026)
This study examines the implementation of a Moodle-based Learning Management System (LMS) and its role in stimulating self-regulated learning (SRL) among students enrolled in a civil service school preparation program at Caping Indonesia, Karanganyar, Central Java. A qualitative descriptive design was employed to explore students’ experiences, learning behaviors, and interactions with Moodle features in a non-formal education setting. Participants consisted of eight students who actively used the LMS and one tutor responsible for monitoring and supporting their learning. Data were collected through semi-structured interviews, direct observation, and documentation analysis of learning activities, login records, module completion, practice tests, and performance reports. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model comprising data condensation, data display, and conclusion drawing or verification. The findings show that Moodle functions not merely as a repository of learning materials but as an integrated learning environment that supports all three phases of Zimmerman’s SRL model. In the forethought phase, structured modules, learning schedules, and targets help students plan and prioritize study activities. During performance control, flexible access, repeated practice, reminders, progress tracking, and tutor monitoring enable students to regulate their learning consistently. In the self-reflection phase, automated scores, detailed feedback, and performance histories allow students to identify weaknesses, review materials, and adjust learning strategies. The study concludes that Moodle can strengthen learner autonomy, metacognitive awareness, and independent learning practices in civil service school preparation. Its effectiveness, however, depends on intentional instructional design, personalized feedback, and the integration of learning analytics within non-formal education contexts.